Analisis Efektifitas Dan Kemampuan Berfikir Kreatif Peserta Didik Melalui Pembelajaran Daring Dimasa Covid-19 Pada Pelajaran Fisika - Riska, Riska; Widyaningsih, Sri Wahyu; Sebayang, Sri Rosepda (Al-Khazini, 2022)
This study aims to analyze the effectiveness and creative thinking of student’s learning throught online learning during the Covid-19 era in physics lessons at SMA Advent Manokwari. The research method used is the survey method using a questionnaire. The sampling technique is using purposive sampling with a sample 79 studens. The instrument used is an effectiveness questionnaire as many as 15 statements and a creative thinking questionnaire as many as 15 statements with data analysis technique using the Rasch Model with the help of the Winstep Application. The results of the analysis show that for learning effectiveness the Crombach Alpha value 0,82, while using Wright map the distribution of respondents generally gathers between logit SD (+0,00) to logit SD (+2,00) and above logit SD (-0,20) this means that many students are interested in taking physics lessons online and consider it good or effective. Meanwhile, for creative thinking, the Crombach Alpha value is 0,76, also using the Wright map the distribution of respondents generally gathers berween the logit SD (+0,00) the logit SD (+3,00) and above the logit SD (-0,30). This means that many students have a high enough creative way of thinking. This shows that online physics lessons at the SMA Advent Manokwari can be said to be good and the student’s creative thinking level is high.